No Associations Between Regular Use of Proton Pump Inhibitors and Risk of All-Cause and Cause-Specific Mortality: A Population-Based Cohort of 0.44 Million Participants. (27th November 2021) - He, Qiangsheng; Xia, Bin; Meng, Wenbo; Fan, Die; Kuo, Zi-Chong; Huang, Junjie; Qin, Xiwen; Zou, Huachun; He, Yulong; Zhang, Changhua; Fang, Shuo; Pan, Yihang; et al.
Abstract : INTRODUCTION: The association between proton pump inhibitors' (PPIs) use and mortality remains unclear. METHODS: This was a prospective analysis of 440, 840 UK residents and 13, 154 deaths. We evaluated the associations with multivariate Cox regression. RESULTS: After adjusting for confounders, such as over health status and longstanding diseases, the regular use of PPIs was not associated with an increased risk of all-cause mortality and mortality due to neoplasms, circulatory system diseases, respiratory system diseases, digestive system diseases, external causes, and other causes. DISCUSSION: Regular use of PPIs was not associated with an increased risk of all-cause and cause-specific mortality. Abstract :